Interlok from a Multiculturalism Perspective (Malay Literature, 2019)
Interlok may be read as a multiculturalism narrative that depicts the process of building a national identity, which develops from a rigid ethnic identity. Through the narrative of social events, an envisioning of a gradual formation of a national identity, situated within a multicultural space is presented by the author. This vision of multiculturalism is perhaps an ideal, but it reflects the author's optimism for a future where a nation can be formed from the unity of its multicultural diversity. This ideal form of multiculturalism goes beyond assimilation as it is indeed a kind of integration that emphasizes on the culture of the majority as the dominant culture. The practice of this dominant culture must be just and equal as it evolves into the ideal national culture. However, this vision may have its detractors. It may give rise to a false identity that differs from the social identity of the real world. Nevertheless, this paper argues that the author's vision for the formation of the ideal national identity in Malaysia's multicultural society is one that is visionary and forward-looking showcasing his effort in promoting positive values in society through literature.Keywords: Abdullah Hussain, Interlok, multiculturalism